Interview with Prof. Dr. Gusztáv Báger - Gábor, Kutasi (Public Finance Quarterly, 2025)
Gusztáv Báger, Professor Emeritus at Pázmány Péter Catholic University, has conducted wide-ranging work and research over the decades. He consistently transformed his practical achievements into contributions to academia, he applied new scientiﬁc ﬁndings in practice. As a department head at the National Planning Office and as an expert at the UN Economic Commission for Europe, he was responsible for the development of complex econometric macroeconomic models. Later, as a department head at the Ministry of Finance, he led the development of economic reform programs. As Director General of the Development and Methodological Institute of the State Audit Office, he played an active role in the development of Hungary’s anti-corruption framework and public sector integrity system, and in shaping public ﬁnancial responsibility.